Exploring the influence of anemia and inflammation indices on colorectal cancer: analysis of the national health and nutrition examination survey From 2011 to 2018 - Qu, Chao; Yang, Shuting; Shen, Tianli; Peng, Qiuting; Sun, Xuejun; Lin, Yuyao (Frontiers in Oncology, 2024)
PurposePatients with colorectal cancer (CRC) frequently present with anemia and signs of infection. However, the relationships between these factors remain unclear. This study investigated the potential association between anemia, inflammatory indices, and CRC.MethodsWe analyzed data from the 2011–2018 National Health and Nutrition Examination Survey to investigate links between anemia, inflammation, and CRC. Inflammatory indices, including the neutrophil-percentage-to-albumin ratio, neutrophil-to-lymphocyte ratio, and eosinophil-to-lymphocyte ratio, were analyzed. Following rigorous inclusion criteria, 14,114 participants were included. Statistical methods such as logistic regression and subgroup analyses were employed. Moreover, survival analysis was performed.ResultsAmong the 14,114 participants, 0.6% had CRC and 11.0% were diagnosed with anemia. Anemia and inflammatory indices were associated with CRC, suggesting an increased risk (OR range: 2.03-2.50, P<0.05). Patients with CRC had lower red blood cell counts, reduced hemoglobin levels, and higher inflammatory indices. This is accompanied by an increase in the inflammatory indices, which is also a risk factor for CRC (OR range: 1.12-7.00, P<0.05). Survival analyses indicated that anemia was associated with lower survival rates, impacting all-cause, cancer, and CRC mortality.ConclusionOur results indicate that anemia and inflammatory indices are correlated with CRC. Patients with CRC tend to exhibit increased inflammatory indices and decreased red blood cell count and albumin levels, potentially impacting survival.